A Flowmeter Technique to Exclude Internal Mammary Artery Anastomosis Error in an Arrested Heart - Hashim, Shahrul Amry; Amin, Mohd Afiq; Nair, Ashvin; Mokhtar, Raja Amin Raja; Krishnasamy, Sivakumar; Cheng, Kenny (Elsevier, 2018)
The revision of an internal mammary artery graft anastomosis because of a technical error can be time-consuming and complicated and may lead to complications. Here, we describe the technical details and our early experience of using a standard transit-time flowmeter to exclude technical errors and facilitate rapid decision making for anastomosis revision in an arrested heart during aortic cross-clamping in the absence of ultrasound guidance.